Mass Transport/Diffusion and Surface Reaction Process with Lattice Boltzmann (Communications in Computational Physics, 2020)
Multi-component flow with chemical reactions is a common problem indifferent industrial applications: the mixing chamber of a reaction injection molding(RIM) machine; the dynamics of diesel soot particles interacting with a porous-ceramicparticulate filter; reactive transport in porous media; bio-chemical processes involvingenzyme-catalyzed kinetics. In all these cases, mass diffusion/convection and wallor volume chemical interactions among components play an important role. In thepresent paper we underline the importance of diffusion/convection/reaction mechanismsin bio-chemical processes using the Lattice Boltzmann (LB) technique. Thebio-application where we studied diffusion/convection/reaction mechanisms is thequorum-sensing pathway for the bio-synthesis of the AI-2, a molecule that allows thebacteria to launch a coordinated attack on a host immune system (see [9, 10] for moredetails of the bio-application). The overall goal is to create a micro-device to screen potentialdrugs that inhibit AI-2 bio-synthesis. The Michaelis-Menten saturation kineticmodel is implemented at the reactive surface and the results are shown in terms of twodimensionless numbers: Damkohler (Da) and Peclet (Pe) number. For high Pe numbera small conversion of reactants into products is obtained at the reactive surface, butthe overall flux of products is high; moreover, a fast saturation of the conversion ofreactants to products is obtained for high Da numbers. The trade-off for setting the Peand Da numbers depends on the specific application and the technologies used in themicro-device (e.g., sensitivity of the detector, cost of reactants).